Quantitative analysis of energy loss and vibration performance in a circulating axial pump. (15th March 2022) - Pu, Kexin; Huang, Bin; Miao, Hongjiang; Shi, Peili; Wu, Dazhuan
Abstract: The influence of vortex on steady flow and pressure fluctuation of circulating axial pump under pump condition is illustrated by numerical method validated by experiment measurement, a method for analyzing vibration by using Euler head density function (EHDF) is established. Based on the matching equation of the flowing angle of impeller and guide vane, two groups of guide vanes are designed to relate the same impeller as comparison. When the stagnation point at the guide vane inlet is offset, the low-speed vortex (LSV) is generated in the area from the mid flow surface to the hub surface, where the local Euler head (LEH) curves' distribution is disarranged and the EHDF of this part is larger and closes to the EHDF value of the whole spanwise region, furthermore, the pressure fluctuation levels of low frequency band here deteriorate seriously. The larger EHDF value means the flow state and pressure fluctuation are worse, and the mainly developing of LSV is in this problematical area where the EHDF value has deteriorated the most. With quantizing image analysis of vorticity and LEH of the circulating pump by the EHDF, the structure position of LSV can be analyzed and the vibration level can be predicted. Highlights: A quantitative analysis method for low frequency fluctuation of axial pump is proposed. The angle design method of rotor-stator interference (RSI) region is put forward. The local Euler head (LEH) distribution in the RSI and guide vane region is analyzed. The Euler head density function (EHDF) is proposed to locate the low-speed vortex. The proposed EHDF is extracted to predict the quality of pressure fluctuation.